1984
DOI: 10.1136/oem.41.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Rice millers' syndrome: a preliminary report.

Abstract: A study was carried out to determine the health effects of rice husk dust in Malaysian rice millers. The study population consisted of 122 male Malay workers from three rice mills, with 42 controls of similar age, sex, ethnic group, and agricultural work background. Interviews using standardised questionnaires, physical examination, total and differential white cell counts, chest radiographs, and lung function tests were performed on each of the millers and the controls. Environmental dust monitoring was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…Nasal symptoms in grain and dust job workers had been mentioned in many studies but the prevalence (64%-14.4%) were higher than our findings (6.4%) 12,17,25,26 . Our lower findings might be for the short duration of exposure or for the less presence of hazardous content including less allergens in the grain dust.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Nasal symptoms in grain and dust job workers had been mentioned in many studies but the prevalence (64%-14.4%) were higher than our findings (6.4%) 12,17,25,26 . Our lower findings might be for the short duration of exposure or for the less presence of hazardous content including less allergens in the grain dust.…”
Section: Discussioncontrasting
confidence: 57%
“…Our lower findings might be for the short duration of exposure or for the less presence of hazardous content including less allergens in the grain dust. Lim H H et al mentioned rice husk dust responsible for nasal catarrh included in as ''Rice millers' syndrome'' in Malaysian in their study 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Malaysian rice millers indicated the possibility of early silicosis due to the silica in rice husk 28) . This study suggests the importance of a detailed characterization of the silica in rice husk and in RHA dust to clarify the cause of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in rice farmers reported the prevalence of respiratory symptoms, such as chronic bronchitis (6.3%), physiciandiagnosed asthma (7.1%), and persistent wheezing (8.8%). 7 The present study demonstrates that rice powder inhalation can induce occupational asthma and rhinitis through an IgE-mediated response, as evidenced by positive responses to rice extract on skin prick and bronchoprovocation tests and the presence of high serum specific IgE levels.…”
Section: Three Cases Of Rice-induced Occupational Asthmamentioning
confidence: 95%